In vitro anti-proliferative effects of the willow bark extract STW 33-I - Bonaterra, Gabriel; Kelber, Olaf; Weiser, Dieter; Metz, Jürgen; Kinscherf, Ralf (Arzneimittelforschung, 2010)
The well-known anti-inflammatory and analgesic effects of the phytopharmacon willow bark extract have been attributed to the content of salicin; however, pharmacological studies have shown that salicin alone, despite being involved in its therapeutic action, cannot fully explain its clinical efficacy. In addition to reducing inflammation and pain, acetylsalicylic acid (ASA, CAS 50-78-2), like other synthetic non-steroidal anti-inflammatory drugs (NSAIDs), has been shown to exert anti-proliferative effects and to induce apoptosis in a variety of cell lines, e. g. colon, stomach, and prostate cancer cells. To investigate the mechanism of action and possible anti-proliferative and pro-apoptotic effects of willow bark, a water extract (STW 33-1) and a polyphenol rich fraction (fraction E) have been tested by using the colon-carcinoma cell line HT-29. Both, STW 33-1 and its fraction E showed significant anti-proliferative and pro-apoptotic effects on HT-29 cancer cells. Related to the salicin content of the willow bark extract, a higher dosage of ASA was needed. Furthermore, compared to ASA and to diclofenac (Diclo, CAS 15307-79-6), the COX-1 and COX-2 mRNA expressions were influenced differently by STW 33-1 and fraction E. ASA and Diclo inhibited both the COX-1 and COX-2 mRNA expressions, whereas STW 33-1 and its fraction E increased the COX-1 mRNA expression. In addition to the already well-known anti-inflammatory and analgesic effects, willow bark extract has been found to possess anti-proliferative and pro-apoptotic effects similar to NSAIDs. The different influence of willow bark on the COX-1 and COX-2 mRNA expressions in comparison to NSAIDs might be relevant, e. g. for prevention of undesirable side effects such as gastric erosions.
Erstmals am 02. Dezember 2011 online veröffentlicht
Gesehen am 08.02.2023